First detection and low prevalence of Pearsonema spp. in wild raccoons (Procyon lotor) from Central Europe. (December 2022) - Heddergott, Mike; Müller, Franz; Steinbach, Peter; Jeschke, Diana; Stubbe, Michael; Frantz, Alain C.; Stubbe, Annegret; Ansorge, Hermann; Osten-Sacken, Natalia
Abstract: The urinary bladder and lower urinary tract of domestic and wild carnivores can be parasitised by filamentous nematodes from the genus Pearsonema (syn. Capillaria ). Infestations are often asymptomatic, but severe courses in dogs and cats have been described. Hosts are infested through the ingestion of earthworms (Lumbricidae) which act as intermediate hosts. Epidemiological studies of Pearsonema in raccoons ( Procyon lotor ) in North America are scarce and previous studies of urinary bladder parasites of European raccoons did not provide evidence of infestation. We examined urine sediment or rinse water from urinary bladders of 499 wild raccoons from Luxembourg, Poland and five study sites in Germany. Pearsonema eggs were found in the urine sediment of 31 (6.2%) raccoons. Infested animals were found in all study areas with prevalence values ranging from 3.7% to 8.7%. No significant difference in prevalence was found either between animals in urban and rural areas or between sexes and age classes. Based on their morphology, the eggs were likely to be P. plica . Considering their increasing density in Central Europe, raccoons may play a previously overlooked role in environmental contamination with Personema eggs. Graphical abstract: Image 1 Highlights: Invasive raccoons are reservoirs for Pearsonema spp. in Central Europe. We tested urinary bladders from 499 raccoons from Luxembourg, Poland and Germany for the presence of Pearsonema eggs. Thirty-one (6.2%) raccoons tested positive, with infections found in all study areas with a low prevalence. This is the first report of Pearsonema spp. in raccoons in Europe and outside their original range in North America.